Fluoride intake from food and beverages by 1to-3-year-old toddlers attending a preventive dental program - Salama, Isabel Cristina Cabral de Assis [UNESP]; Dezan, Cássia Cilene; Hosida, Thayse Yumi [UNESP]; Ferraresso, Lucas Fernando Oliveira Tomáz [UNESP]; Sampaio, Caio [UNESP]; Mancilla, Jorge Orlando Francisco Cuéllar; Nagata, Mariana Emi; Pessan, Juliano Pelim [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP] (My University, 2025)
Purpose: To evaluate fluoride (F) intake by 1–3-year-old children from the diet, as well as F concentrations in fingernails and toenails. Methods: Twelve-month-old Children (n=202), participants in a Preventive Dental Program for infants, had their F ingestion monitored by means of the application of a semi-quantitative food frequency questionnaire (FFQ), composed of 70 items, divided into 9 groups of foodstuffs. The FFQ was applied for 2 years, every 3 months, along with the collection of diet, nails and water samples used for drinking and food preparation. The concentration of F in the diet, nails, and water was determined with an ion-specific electrode, after hexamethyldisilane-facilitated microdiffusion or by the direct method. The data obtained were submitted to the 2-way analysis of variance, followed by the Student-Newman-Keuls’ test, and by Spearman correlation coefficient (p<0.05). Results: The average ingestion of F by diet and water was significantly higher from 12 to 24 months (0.015 mg F/Kg/day and 0.09 mg F/Kg/day) compared with values obtained after 27 months (0.011 mg F/Kg/day and 0.05 mg F/Kg/day) (p<0.05). At 36 months, a peak of F ingestion from the diet (0.013 mg F/Kg/day) (p<0.05) was observed. There was a continuous increase in F levels in finger-and toenails, with a significant difference in some periods of the study (18 to 27 months, p<0.05); higher F concentrations were observed for fingernails over toenails (3.7 µg F/g; 3.4 µg F/g, respectively, p<0.05). No significant correlation was observed between the estimate of ingestion of fluoride related to the weight of the child (mg F/kg/day) and the fluoride in fingernails (Spearman’s r = 0.024; p=0.396) or toenails (Spearman’s r =-0.002; p=0.957). Conclusions: The ingestion of fluoride from the diet in 1–3-year-old children was shown to fall within safe limits, and the FFQ appears to be a satisfactory tool to estimate the ingestion of fluoride. Small variations of daily ingestion of F by diet were detected in the nails through the periods in the study (after 30 to 60 days).
Keywords: Child; Enamel Fluorosis; Fluoride; Nail